Pemberdayaan Komunitas Sekolah dalam Pengembangan Budaya Antibullying dan Etika Digital di Era Media Sosial - Man Arfa, Arman; Lasaiba, Djamila; lasaiba, Irvan (Universitas Pattimura, 2024)
The rise of digital technology has reshaped social interaction patterns in educational environments, bringing new challenges such as the increase in online bullying cases and the lack of digital ethics awareness among school communities. This community service aims to empower schools by strengthening the capacities of teachers, students, and parents to establish a sustainable culture of anti-bullying and digital ethics. The participatory school-based approach involved situation analysis, training, mentoring, and reflective evaluation. The results demonstrate a significant improvement in digital ethics awareness, teachers’ ability to detect early signs of bullying, and students’ active participation as digital peace ambassadors. Furthermore, parents became more engaged in supervising values at home, fostering a strong connection between family and school. The program presents an effective collaborative model for cultivating positive digital behavior and building a digitally responsible school ecosystem. Its implication suggests that this model can be replicated in other schools as a preventive and character-based digital education strategy